Effect of Cinnamaldehyde Addition on Injectable Gypsum–Calcium Carbonate Hydrogel Paste with Ultraviolet Light Polymerization: Bone Scaffold Material for Implant - Dewi, Anne Handrini; Pridatama, Muhammad Akhsan; Arum, Dena Kusuma; Mohktar, Mas Sahidayana; Kusuma, Hersandy Dayu; Triawan, Andi (European Journal of Dentistry, 2025)
Hydrogel-based, gypsum, calcium carbonate (CaCO3) bone scaffolding materials and antibacterial extracts from cinnamaldehyde herbal ingredients are a combination of smart materials that are abundant and environmental friendly. That component is a promising candidate for bone scaffold material. This prototype has been designed as an injectable paste that is easy to apply, fills in bone and dental defects, and quickly polymerizes with the help of ultraviolet (UV) light. The purpose of this study is to investigate the effects of adding cinnamaldehyde to injectable gypsum–CaCO3 hydrogel paste that has undergone UV light polymerization for biodegradable implant material.A composite material was synthesized named Cia by a combination of gelatin, gypsum, CaCO3, and cinnamaldehyde compound assisted by UV light polymerization. An in vitro and in vivo quasi-experiments were conducted in this study, including material characterization and testing. Material characterization was performed using Fourier transform infrared spectroscopy) and scanning electron microscope. Material testing examined the swelling ratio and degradation rate. Antibacterial activity was performed as in vitro testing undergone Streptococcus sanguinis and Pseudomonas aeruginosa. Data were analyzed statistically using an independent t-test (p < 0.05). A total of 21 male Wistar rats were used in vivo study. A femoral condyle was chosen as a hard tissue representative of the jaw. Tissues were then stained with hematoxylin–eosin and Mallory staining observed under a light microscope to identify the tissue regeneration and implant remaining.Synthesized material that is added by cinnamaldehyde could be an implant material for inducing tissue regeneration.
Keywords: cinnamaldehyde; injectable paste; ultraviolet; polymerization; scaffold; implant